The Effectiveness of the Among Us Game in Enhancing EFL Students' Speaking Skills - kevin Hendrawan; Alifiah Pratiwi; Heri Alfian; Kadaruddin; Susi Astiantih; Muhammad Irfan Rahim (Universitas Islam Negeri Palopo, 2026)
This study aimed to investigate the effectiveness of the Among Us game in enhancing EFL students' speaking skills and to explore their perceptions of its implementation in speaking classes. The study employed a mixed-methods approach with a one-group pre-test–post-test pre-experimental design. Although 25 students initially participated, only 12 students completed all stages of the study and were included in the quantitative analysis. Quantitative data were collected through speaking performance tests administered before and after the intervention, while qualitative data were obtained through semi-structured interviews with five participants. The quantitative data were analyzed using descriptive statistics, intraclass correlation coefficient (ICC), the Shapiro–Wilk normality test, a paired-sample t-test, and normalized gain (N-Gain) analysis, while the qualitative data were analyzed using narrative analysis. The results indicated a medium level of improvement in students' speaking performance based on the mean N-Gain score of 0.4715. The qualitative findings represented students' perceptions and indicated that they became more willing to communicate, perceived improvements in their speaking performance, and developed greater self-confidence when using English in classroom activities. The novelty of this study lies in combining empirical evidence from pre- and post-intervention speaking performance with students' reported learning experiences to provide a more comprehensive understanding of the implementation of Among Us in EFL speaking instruction. These findings suggest that the Among Us game has potential as a game-based learning medium for creating an engaging, interactive, and communicative environment that supports EFL speaking instruction.